Pengaruh DER dan ROA Terhadap Harga Saham Dengan PER Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Pertambangan Logam Dan Mineral - Wilton Pratama; Novi Permata Indah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
Metal and Mineral mining sub-sector companies are one of the sectors that contribute high growth to the Indonesian market capitalization. The existence of new innovations in the automotive world, especially electric cars, which require metal and mineral raw materials as electric batteries for propulsion, this adds fresh air to the metal and mineral mining sector in Indonesia. However, over time the Metal and Mineral mining sector experiencing ups and downs. This study intends to determine, test and analyze the effect of DER, and ROA, on stock prices with PER as a moderating variable in Metal and Mineral mining sub-sector companies listed on the IDX for the 2016-2020 period. The research method used is descriptive verification. The population is Metal and Mineral mining sub-sector companies listed on the IDX. The sampling technique used was purposive sampling which resulted in 9 out of 13 companies. The analysis tool uses multiple linear regression and moderated regression analysis. The results of the study explain that partially DER and ROA affect stock prices, as well as simultaneously DER and ROA affect stock prices. PER is not able to moderate the effect of DER and ROA on stock prices. The regression model obtained by Adjusted R Square is 18.1% with the remaining 81.9% influenced by other variables not examined. Keywords: debt to equity ratio;price earning ratio;return on asset;stock prices.